2008
DOI: 10.1007/s00775-008-0460-x
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium polypyridyl complexes and their modes of interaction with DNA: Is there a correlation between these interactions and the antitumor activity of the compounds?

Abstract: Various interaction modes between a group of six ruthenium polypyridyl complexes and DNA have been studied using a number of spectroscopic techniques. Five mononuclear species were selected with formula [Ru(tpy)L1L2](2−n)+, and one closely related dinuclear cation of formula [{Ru(apy)(tpy)}2{μ-H2N(CH2)6NH2}]4+. The ligand tpy is 2,2′:6′,2″-terpyridine and the ligand L1 is a bidentate ligand, namely, apy (2,2′-azobispyridine), 2-phenylazopyridine, or 2-phenylpyridinylmethylene amine. The ligand L2 is a labile m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 70 publications
(62 reference statements)
6
39
0
2
Order By: Relevance
“…[10] To date, inert dinuclear polypyridylruthenium(II) complexes have only shown modest anticancer activity. [12][13][14] While there are a variety of possible modes of binding available (e.g., intercalation, groove binding, etc. ), there are indications that the cytotoxicity of dinuclear complexes can be significantly enhanced by the incorporation of labile ligands that allow the formation of covalent adducts with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[10] To date, inert dinuclear polypyridylruthenium(II) complexes have only shown modest anticancer activity. [12][13][14] While there are a variety of possible modes of binding available (e.g., intercalation, groove binding, etc. ), there are indications that the cytotoxicity of dinuclear complexes can be significantly enhanced by the incorporation of labile ligands that allow the formation of covalent adducts with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…+ containing different N-donor chelating ligands (N-N), such as bpy, 23,24 1,10-phenanthroline (phen), [23][24][25] 3,4,7,8-tetramethyl-1,10-phenanthroline (tmephen), 26 dipyrido(3,2-a:2′,3′-c]phenazine (dppz), 24,26 N,N,N′,N′-tetramethylethylenediamine (tmen), 23, 26 2,2′-azobispyridine (apy), 27 azpy, 28 have been prepared and studied for their DNA binding ability. It was found that most of the Ru(II)-tpy complexes are capable of binding covalently to DNA (mainly at guanine residues) forming monofunctional adducts and DNA replication was stopped by some of them.…”
Section: Introductionmentioning
confidence: 99%
“…The IC 50 results obtained for both control platinum complexes against both cell lines are consistent with previous studies. [21,28,29] While all the Cl-Irbb n complexes showed relatively poor activity against the MCF-7 cell line, the Cl-Irbb 12 and Cl-Irbb 16 complexes exhibited good activity against the MDA-MB-231 cell line. In all cases, the activity of the Cl-Irbb n complexes increased with the number of carbon atoms in the linking chain.…”
Section: Anticancer Activitymentioning
confidence: 93%